1x+(-2x)+1=(-2x)+3-(-1)

Simple and best practice solution for 1x+(-2x)+1=(-2x)+3-(-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x+(-2x)+1=(-2x)+3-(-1) equation:



1x+(-2x)+1=(-2x)+3-(-1)
We move all terms to the left:
1x+(-2x)+1-((-2x)+3-(-1))=0
We add all the numbers together, and all the variables
x+(-2x)-((-2x)+3-(-1))+1=0
We get rid of parentheses
x-2x-((-2x)+3-(-1))+1=0
We calculate terms in parentheses: -((-2x)+3-(-1)), so:
(-2x)+3-(-1)
We add all the numbers together, and all the variables
(-2x)+4
We get rid of parentheses
-2x+4
Back to the equation:
-(-2x+4)
We add all the numbers together, and all the variables
-1x-(-2x+4)+1=0
We get rid of parentheses
-1x+2x-4+1=0
We add all the numbers together, and all the variables
x-3=0
We move all terms containing x to the left, all other terms to the right
x=3

See similar equations:

| 7x=8+3x+28 | | 8x-48=3x-11+25 | | 2x-9=-3×+21 | | 2x-8=19-x | | -5(x-2)+(x+4)=50 | | (2x+30)+(3x-45)=180 | | 7(p-80)=49 | | 3x+1+x+14+4x+5=180 | | -4(d-5)=-64 | | 20+4^2x=36 | | 4x10=2x+60 | | 7=d/3+4 | | -4p+9=-3.7 | | (2x)/(x+9)=(5)/(4) | | 12=-(3/5)u | | -24=m-18 | | 5x-2x+8=28 | | u/3+15=19 | | 2(2x-1)+3=7+3x | | C(x)=20.25-0.20x | | 5x+10-2x=+37 | | 4(v+8)=8 | | 29v+7=11 | | 1h=252 | | 12=(-3/5)u | | 22=6+m | | 5x+10-2x=1+37 | | 12=(-(3/5))u | | 6-4+x+12+3x+2=180 | | 22=6×m | | 6m+17-5m=50 | | m/3-6=11 |

Equations solver categories